Zen Buddhism in Japanese poetry - Балакаева, Л. Т.; Османова, М. С. (Journal of Oriental Studies, 2017)
This article attempts to examine the impact of Zen-buddizm on Japanese poetry.The definition of the concept of Zen-buddizm, its ideological principles. Reveals the origins of Zen -buddizm, its influence on Japanese culture. Emphasis is placed on the reflection of the ideas of zen-buddhism in the creation of the famous Japanese poet Matsuo Basho as well as traditional Japanese poetry haikai genre.